IMPLEMENTASI MASSAGE EFFLEURAGE UNTUK MENURUNKAN SKALA NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI POLI OBGYN RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Gustina, Erita; Atsnia, Atsnia; Af’idah, Huwaina (SINERGI : Jurnal Riset Ilmiah, 2025)
Pregnancy causes various physiological changes, including in the musculoskeletal system, which often trigger complaints of back pain, particularly in the third trimester. This pain can interfere with the comfort and quality of life of pregnant women. One non-pharmacological intervention that can be used to reduce pain is effleurage massage therapy. This study aims to implement the therapy to reduce the back pain scale in third-trimester pregnant women at the Obstetrics and Gynecology Clinic of Tk II Putri Hijau Hospital, Medan. The research method used is a descriptive case study on two patients, using a maternity nursing care approach from assessment to evaluation. Inclusion criteria included third-trimester pregnant women (28–40 weeks) who are primigravida, experiencing back pain, and not having any comorbidities or obstetric complications. The intervention was carried out for three consecutive days, each session lasting 15 minutes, with evaluation using the Numeric Rating Scale (NRS). The results showed a decrease in pain levels from moderate (6 and 5) to mild (2 and 1). In conclusion, effleurage massage is effective in reducing back pain in third-trimester pregnant women. This study is expected to serve as a reference for future research to further explore the effectiveness of this therapy more broadly and measurably.